Multipole Multi-Layered Magnetorheological Brake with Intermediate Slots - Yaojung Shiao; Mahendra Babu Kantipudi (Applied Sciences)
Magnetorheological (MR) brakes are flourishing in low-torque applications due to their dynamic controllability nature. Researchers have introduced multi-layer and multipole concepts to increase the torque–volume ratio (TVR) of the MR brake. However, the combination of these two ideas did not exist due to the design limitations. Therefore, this study aims to design a brake that combines the multipole magnetic field and multi-layered structure concepts. The axial slots were introduced on the brake rotor and the stator drum axial surfaces to achieve a high TVR. These slots stop the flux bypass in the inner layers; therefore, the magnetic flux can also reach the brake’s outer layers. This brake was designed with multiple stator and rotor drums and MR fluid layers. The number of poles was placed so that the magnetic field from these poles traveled in a closed loop via the stator, rotor, and MR layers. A 3D model of the brake was prepared for the virtual study. Electromagnetic simulations were conducted to analyze the effect of axial slots’ and other design parameters of the brake. According to those simulation results, the axial slots’ width and position significantly affect the brake output torque. The maximum torque obtained from the brake is 38 Nm, and the TVR value of the brake is 41 Nm/dm3. Additionally, multiphysics simulations were performed to understand the Joule-heating effect of the magnetic coil and the frictional heating in MR fluid. Results showed that the maximum possible temperature in the brake is under the MR fluid temperature limits. Therefore, this multipole multi-layered (MPML) MR brake with axial slots idea is very useful for high-torque MR brake growth.